SGLT2 Inhibitors and Diabetic Kidney Disease: Targeting Multiple and Interrelated Signaling Pathways for Renal Protection - Papaetis, Georgios S. (Current Molecular Pharmacology, 2024)
Almost 20-40% of all patients suffering from diabetes mellitus experience chronic kidney disease, which is related to higher mortality (cardiovascular and all-cause). The implication of several pathophysiological mechanisms (hemodynamic, tubular, metabolic and inflammatory) in the pathogenesis of diabetic kidney disease generates an urgent need to develop multitarget therapeutic strategies to face its development and progression. SGLT2 inhibitors are undoubtedly a practice-changing drug class for individuals who experience type 2 diabetes and diabetic kidney disease. In vitro studies, exploratory research, sub-analyses of large randomized controlled trials, and investigation of several biomarkers have demonstrated that SGLT2 inhibitors achieved multiple beneficial activities, targeting several renal cellular and molecular pathways independent of their antihyperglycemic activity. These mainly include the reduction in intraglomerular pressure through the restoration of TGF, impacts on the renin-angiotensin-aldosterone system, improvement of renal hypoxia, adaptive metabolic alterations in substrate use/energy expenditure, improvement of mitochondrial dysfunction, and reduction of inflammation, oxidative stress and fibrosis. This manuscript thoroughly investigates the possible mechanisms that underlie their salutary renal effects in patients with diabetes, focusing on several pathways involved and the interplay between them. It also explores their upcoming role in ameliorating the evolution of chronic kidney disease in patients with diabetes.
Keywords: Glucosuria